THE ROLE OF JOB EMBEDDEDNESS AND NURSE SELF LEADERSHIP IN IMPROVING RETENTION THROUGH IMPORTANCE-PERFORMANCE MAP ANALYSIS - Waloni, Febryna; Antonio, Ferdi (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Abstract This study analyses the role of job embeddedness and nurse self-leadership in improving retention in private hospitals, using Importance–Performance Map Analysis (IPMA) to identify strategic priorities. A cross-sectional survey of 138 skilled nurses from two accredited private hospitals was conducted. Data from validated questionnaires were analysed using PLS-SEM with IPMA extension. Job embeddedness significantly enhanced self-leadership and directly increased intention to stay. IPMA identified incentive adequacy, perceived sacrifice of leaving, self-development opportunities, and interpersonal relationships as high-importance but underperforming factors. High-performing strengths such as skill utilization were also noted. Hospitals should enhance incentives, career pathways, recognition, and team cohesion to strengthen both economic and emotional embeddedness. Integrating job embeddedness and self-leadership within the IPMA framework provides actionable, evidence-based insights for improving nurse retention in competitive healthcare settings. Keywords: Importance-Performance Map Analysis, Job Embeddedness, Nurse Self-Leadership, Retention, PLS-SEM